Working conditions in Europe: The role of global value chains and advanced digital production-driven technological specialisation - Dagmara Nikulin; Aleksandra Parteka; Joanna Wolszczak-Derlacz (European Trade Union Institute (ETUI), 2022)
This paper's analysis of working conditions in Europe compares several aspects of job quality and wages, rather than relying on earnings as a sole indicator of workers' well-being.We use a micro-level database of workers from 22 European countries to assess how global value chains (GVCs) and advanced digital production (ADP) technologies affect working conditions. We show that the estimated link between GVC involvement and working conditions is conditional on the technological content of the job: the two aspects should not be analysed separately. The exact effect varies across types of technological exposures and particular aspects of job quality. In occupations of high software and robot exposure, job quality tends to deteriorate as GVC involvement increases. This effect is largely negligible for monetary wages. However, we argue that wages for low software, robot and AI-exposed occupations decrease with GVC intensity.
Keywords: F1; F6; J8; O33; 330; working conditions; global value chains (GVCs); advanced digitalproduction (ADP) technological specialisation